How external factors (e.g. climate change, conflicts, socio-economics, trading patterns) will impact veterinary services and the adaptations required - Grace, Delia; Caminiti, A.; Torres, G.; Messori, S.; Bett, Bernard K.; Hu Suk Lee; Roesel, Kristina; Smith, Jimmy W. (World Organisation for Animal Health, 2019)
This Technical Item addressed the question of how External Factors (e.g. climate change, conflicts, socioeconomics, trading patterns) will impact Veterinary Services over the next ten years and the Adaptations required. Information gathering centred on a questionnaire sent to OIE Member Countries but included expert elicitation, a scenario-building workshop, and a complementary questionnaire send to external stakeholders. The response rate to the OIE Member Country Questionnaire was high (74%) and balanced across OIE regions and income categories. A long-list of 59 External Factors highly relevant to Veterinary Services was developed through a structured Expert Survey. The most relevant 17 External Factors were evaluated by OIE Member Countries and Stakeholders. There was overall high level of concern over External Factors, good levels of knowledge, less current activities (Adaptation) and even less activities oriented towards future change (Preparedness). The high agreement of OIE Member Countries with Stakeholders supports the external validity of these assessments. Both OIE Member Countries and Stakeholders judged Veterinary Services to have appropriate priorities, high levels of capacity, and strong influence; both groups of respondents also see opportunities to further strengthen these. Through scenario planning, a preferred future ‘Green Growth with Equity’ was identified along with suggestions for what Veterinary Services could do to help bring this about. OIE Member Countries reported on the current future-oriented activities of Veterinary Services, showing overall high engagement in general planning and disease and health risk assessments, but less use of institutional risk assessment or formal Foresight studies. However, they assessed these as highly important for Veterinary Services, thus implicating a gap which needs to be overcome so that Veterinary Services can be best prepared for an uncertain future. OIE Member Countries identified and ranked actions that could support the capacity of Veterinary Services for Foresight and Adaptation, including areas which the OIE would lead.